Characterization and functional validation of β-carotene hydroxylase gene AcBCHs in Actinidia chinensis. Issue 1 (14th March 2022) - Xia, Hui; Zhou, Yuanjie; Lin, Zhiyi; Guo, Yuqi; Liu, Xinling; Wang, Tong; Wang, Jin; Deng, Honghong; Lin, Lijin; Deng, Qunxian; Lv, Xiulan; Xu, Kunfu; et al.
Abstract: Carotenoids are the pigment substance of yellow-fleshed kiwifruit, among which β-cryptoxanthin was only detected in the brighter yellow-fleshed variety "Jinshi 1". β-carotene hydroxylase (BCH) catalyzes the formation of β-cryptoxanthin and zeaxanthin, but its molecular characteristics and functions have not been fully explained. Here, we isolated two β-carotene hydroxylase genes, AcBCH1 and AcBCH2 from kiwifruit ( Actinidia chinensis ), and their relative expression levels exhibited a close correlation with the content of β-cryptoxanthin. AcBCH1 catalyzed the formation of β-cryptoxanthin when transformed into the β-carotene-accumulating yeast cell. Moreover, silenced expression of AcBCH1 in kiwifruit caused a decrease in the contents of zeaxanthin, lutein and β-cryptoxanthin, and an increase in β-carotene content. The content of β-carotene decreased significantly after AcBCH1/2 were overexpressed in tomato. The content of zeaxanthin increased and β-carotene decreased in transgenic kiwifruit seedlings. The results will enrich our knowledge of the molecular mechanisms of carotenoids biosynthesis in kiwifruit.